Acts and Resolves Passed by the General Assembly of the State of Rhode Island 64-66 (1909) - (:unkn) unknown (My University, 1909)
Ch. 394, §§ 89-90: No body of men, other than the organized militia, the organized naval forces, the independent chartered military organizations, the military and naval forces of the United States, associations wholly composed of soldiers, sailors, or marines, honorably discharged from the service of the United States, veterans of the national guard or naval militia, the organizations of the order of the sons of veterans, and organizations now authorized to do so by the express permission of the commander-in-chief or otherwise by law, shall associate themselves together as a military company or organization, or parade in public with firearms in any city or town of this state.
Keywords: MILITIAS